The psychology and rationality of decisions from experience. - Hertwig, Ralph (Synthese, 2012)
Most investigations into how people make risky choices have employed a simple drosophila: monetary gambles involving stated outcomes and probabilities. People are asked to make decisions from description. When people decide whether to back up their computer hard drive, cross a busy street, or go out on a date, however, they do not enjoy the convenience of stated outcomes and probabilities. People make such decisions either in the void of ignorance or in the twilight of their own often limited experience of such real-world options. In the latter case, they make decisions from experience. Recent research has consistently documented that decisions from description and decisions from experience can lead to substantially different choices. Key in this description-experience gap is people's treatment of rare events. In this paper, I briefly review studies that have documented the description-experience gap, offer several explanations for this gap, and discuss to what extent people's decisions from experience are in conflict with benchmarks of rationality.